Assessing and advancing gender equality in agrifood value chains: A toolkit for firms and voluntary sustainability systems - Elias, Marlene; Morgan, Miranda; Nguyen-perperidis, Emily Minhduc; Ronchi, Loraine; Shijagurumay, Meghajit; Soto, Fernanda; Wiegel, Jennifer Rebecca (2023)
this toolkit aims to improve gender equality and women’s livelihoods through agrifood value chain development and programming but proposing a methodology to firms and VSS to: 1. Identify the different groups of actors involved in the upstream (producer, processor, trader) nodes of agrifood value chains - with emphasis on hidden or marginalized groups - and the specific roles, contributions, and benefits of these groups in/from the value chain; 2. Identify the specific barriers these differentiated actors experience in the value chain; 3. Find entry points to create a more enabling environment for these groups and/or for tailored programming to support them.